Generative AI-Driven Metaverse: The Promises and Challenges of AI-Generated Content - Lamiaa Basyoni (16896426) (2025)
Recent advancements in Artificial Intelligence (AI) and immersive technologies, such as Extended Reality (XR), coupled with complementary innovations like 5G/6G wireless communications, are paving the way for fully realized AI-XR metaverses. AI will play a pivotal role in this transformation, enabling the seamless convergence of virtual and physical worlds. Among the various AI applications, Generative AI (GenAI) stands out for creating rich, dynamic, and interactive virtual environments—essential elements for sustained metaverse growth and user engagement. To facilitate a deeper understanding of how GenAI will be integrated and utilized within the metaverse, we provide a comprehensive overview of GenAI and Artificial Intelligence-Generated Content (AIGC). Specifically, we examine the potential influence of GenAI's on future metaverses, exploring both the opportunities it offers and the major challenges associated with its deployment. Additionally, we investigate the robustness of AIGC detection techniques against adversarial attacks, highlighting less-explored risks posed by adversarial examples. Finally, we highlight various open research issues related to GenAI, AIGC, the metaverse, and responsible innovation that merit further exploration. Other Information Published in: IEEE Open Journal of the Computer Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/ojcs.2025.3616501